2008
DOI: 10.1128/aem.01712-08
|View full text |Cite
|
Sign up to set email alerts
|

Murein Hydrolase Activity in the Surface Layer of Lactobacillus acidophilus ATCC 4356

Abstract: We describe a new enzymatic functionality for the surface layer (S-layer) of Lactobacillus acidophilus ATCC 4356, namely, an endopeptidase activity against the cell wall of Salmonella enterica serovar Newport, assayed via zymograms and identified by Western blotting. Based on amino acid sequence comparisons, the hydrolase activity was predicted to be located at the C terminus. Subsequent cloning and expression of the C-terminal domain in Bacillus subtilis resulted in the functional verification of the enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…17 It has previously been reported that although deletion of the cell wall targeting domain of lysostaphin does not interfere Zymography is a method to detect cell wall hydrolase activity on dead cells impregnated in the SDS-PAGE. 37 Our observations of P301 demonstrating activity only on zymogram gel with no CFU reduction are similar to those of Sass and Bierbaum 38 and Raltson et al 39 for a phage endolysin. It is tempting to speculate that the zymogram positive reaction with the P301 protein could be due to the extended time of exposure (more than 16 h) of the protein to the impregnated substrate while the insignificant activity of P301 in the viability assay (CFU drop) ( Table 1) could be attributed to less exposure of the P301 protein to the live cells (1 h) during the viability assay experimental conditions.…”
Section: Discussionsupporting
confidence: 88%
“…17 It has previously been reported that although deletion of the cell wall targeting domain of lysostaphin does not interfere Zymography is a method to detect cell wall hydrolase activity on dead cells impregnated in the SDS-PAGE. 37 Our observations of P301 demonstrating activity only on zymogram gel with no CFU reduction are similar to those of Sass and Bierbaum 38 and Raltson et al 39 for a phage endolysin. It is tempting to speculate that the zymogram positive reaction with the P301 protein could be due to the extended time of exposure (more than 16 h) of the protein to the impregnated substrate while the insignificant activity of P301 in the viability assay (CFU drop) ( Table 1) could be attributed to less exposure of the P301 protein to the live cells (1 h) during the viability assay experimental conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning the Gram-negative Salmonella enterica, a peculiar behavior was observed: while whole cells suspended in buffer were lysed by the sole presence of S-layer (17), no lytic effect was observed when exponentially growing cultures were treated even with both S-layer and nisin (data not shown). However, the S-layer protein remains intact after incubation with whole cells as observed by Western blotting after 8 h of incubation (Fig.…”
mentioning
confidence: 99%
“…For this purpose, the antibacterial activity of S-layer from Lactobacillus acidophilus ATCC 4356, either alone or in combination with nisin, was analyzed using three models of food-borne pathogenic bacteria: Salmonella enterica serovar Newport (10), Staphylococcus aureus ATCC 6538 (used as a representative of Gram-positive bacteria in standard medium tests; laboratory collection), and Bacillus cereus 6A1 (Bacillus Genetic Stock Center [BGSC]). The S-layer proteins were extracted as previously described (17) and conserved as a 1-mg/ml suspension in sterile distilled water at Ϫ20°C until use. Purity was determined by SDS-PAGE as a unique band and detected by Western blotting.…”
mentioning
confidence: 99%
“…S-layers have been shown to have roles in the determination and maintenance of cell shape as virulence factors, as mediators of cell adhesion, and as regulators of immature dendritic and T cells. Moreover, they can also function as a protective coat, molecular sieve, murein hydrolase, and ion trap (4,8,13,17,19,25,29).…”
mentioning
confidence: 99%